Quantification of aeropian and anaerobic metabolism of alcoholic yeast under different environmental conditions - Venturini Filho, Waldemar Gastoni [UNESP]; Figueira, Ricardo [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Auer, Sophia; de Andrade, Thalia Lee Lopes [UNESP] (Universidade Federal do Paraná, 2018)
The aim of this work was quantify the aerobic metabolism (respiration) and anaerobic metabolism (alcoholic fermentation) of yeast at different environmental conditions and different cellular concentration. For this study that was made in bench scale were used musts (15°Brix) produced from cane juice and bread dry yeast Saccharomyces cerevisiae maintained in submerged cultivation. The environmental conditions and cellular concentrations studied were: a) aerobiosis vs. anaerobiosis; b) quantity of inoculum (100, 200 and 300 g.L-1); c) must enriched with ammonium sulphate (0.00; 0.01 and 0.02 M); d) must with different initial pH (4, 5 and 6). Statistical analysis were made using variance analysis and the averages were compared by t Test (assay with two treatments) and Tukey test (assays with three treatments). The alcoholic yeast used in this work showed respirofermentative metabolism and it was classified as facultative anaerobic of the fermentative type. The yeast’s respirofermentative metabolism was changed by the cellular concentrations, pH, enrichment with ammonium sulfate and aerobic and anaerobic conditions of must. By its simplicity, the assays described in this work can be used for teaching purposes.
Quantificação do metabolismo aeróbio e anaeróbio de levedura alcoólica sob diferentes condições ambientais
Keywords: Catabolism; Fermentation; Respiration